Physicochemical Properties and Sensory Preference of Keropok Lekorwith Partial Replacement of Fish Flesh with Oyster Mushroom - Lokman Iqmal-Afifi; Nurzazarina Ramly; Norlelawati Arifin; Nur Huda Faujan (USIM Press, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 9 No 2 Page (128-135)